Kajian Terhadap Hak Eksklusif Atas Jingle Dari Perspektif Hak Cipta Dan Merek - Hosiana Daniel Adrian Gultom; Ellora Sukardi; Serlly Waileruny (Universitas Serang Raya, 2021)
Jingle is included in the category of creation in the form of songs or music under copyright law and is included in the type of sound mark in trademark law. Therefor there is a double legal protection for the jingle, namely copyright and trademark. Copyright law protection uses a declarative system while trademark law protection uses a constitutive system. In copyright law and trademark law there are exclusive rights, namely rights granted by the state to the rightful owner. Exclusive rights in copyright are moral rights and economic rights while exclusive rights in trademarks are called trademark rights. With the existence of moral rights and economic rights in the context of copyright law and rights to trademarks in the context of trademark law, various privileges arise for the owner of the jingle. These features are reviewed by the author in this paper with the aim that the jingle owner can understand the moral rights and economic rights in the copyright law system and the rights to trademarks in the trademark legal system that are related to the jingle in a precise and comprehensive manner.